Optical coherence tomography – near infrared spectroscopy system and catheter for intravascular imaging - Fard, Ali M. (Optical Society of America, 2013)
Owing to its superior resolution, intravascular optical coherence tomography (IVOCT) is a promising tool for imaging the microstructure of coronary artery walls. However, IVOCT does not identify chemicals and molecules in the tissue, which is required for a more complete understanding and accurate diagnosis of coronary disease. Here we present a dual-modality imaging system and catheter that uniquely combines IVOCT with diffuse near-infrared spectroscopy (NIRS) in a single dual-modality imaging device for simultaneous acquisition of microstructural and compositional information. As a proof-of-concept demonstration, the device has been used to visualize co-incident microstructural and spectroscopic information obtained from a diseased cadaver human coronary artery.